2015
DOI: 10.1111/vop.12286
|View full text |Cite
|
Sign up to set email alerts
|

Pocket technique or pocket technique combined with modified orbital rim anchorage for the replacement of a prolapsed gland of the third eyelid in dogs: 353 dogs

Abstract: The aim of this retrospective study was to evaluate the results obtained in 353 dogs (420 eyes) using two different surgical techniques for correction of a prolapsed gland of the third eyelid: the Morgan's pocket technique and a technique combining Morgan's approach with a slightly modified periosteal anchoring technique of Stanley and Kaswan. The pocket technique was used in 234 eyes and the combined technique in 186 eyes. Successful repositioning was obtained in 95% of all cases, with recurrence occurring in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 12 publications
4
36
0
4
Order By: Relevance
“…Similar to previous reports, English bulldogs were over‐represented in the present study . This supports the hypothesis of hereditary predisposition.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Similar to previous reports, English bulldogs were over‐represented in the present study . This supports the hypothesis of hereditary predisposition.…”
Section: Discussionsupporting
confidence: 92%
“…Sapienza et al reported a 100% successful outcome in 122 eyes using an anchoring technique to the ventral rectus muscle . Multari et al reported a series of 109 eyes affected by PGCD with a 93.6% success rate regardless of the technique used . In the present study, MPTC and MPTC + WC achieved, respectively, a 91.6% and a 100% success rate with no significant difference between both techniques.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations